Restrictiveness of services trade policy and the sustainable development goals - Matteo Fiorini; Bernard M. Hoekman (Asian Development Bank Institute (ADBI), 2018)
The realization of many of the United Nations (UN) sustainable development goals (SDGs) depends on bolstering the performance of service sectors and improving access to specific services in developing countries. We show that prevailing services, trade, and investment policies affect access to services that matter for the realization of a number of SDGs: lower trade restrictiveness is an instrument that can enhance the performance of domestic services sectors. This implies that pursuit of the UN's SDGs should include a focus on facilitating trade and investment in services.
Keywords: L8; O10; O24; 330; services; trade policy; sustainable development goals